The Influence of Eye-Hand Coordination, Nutritional Status and the Object Control Ability of Early Childhood - haningsih, widia oktri; Ihsan, Nurul; Gusril, Gusril; Bahtra, Ridho; Andika, Heru (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research aims to see and reveal the relationship between hand eye coordination and nutritional status on children's motor skills. The method used in this research is a quantitative method using an ex-post facto design. The sample in this study consisted of 30 children consisting of 15 boys and 15 girls who were still in kindergarten aged 5-6 years. The data analysis technique used is path analysis. The results obtained in this study show that there is an influence between eye-hand coordination and object control abilities in kindergarten children and there is an influence of nutritional status on object control abilities of children in kindergarten. From the results of the research, there is an influence between hand word coordination and nutritional status on control objects in children who are still in kindergarten (TK).